Reducing behavioral health symptoms by addressing minority stressors in LGBTQ adolescents: a randomized controlled trial of Proud & Empowered - Jeremy T. Goldbach; Harmony Rhoades; Mary Rose Mamey; John Senese; Peter Karys; Flavio F. Marsiglia (BMC, 2021)
Abstract Background Minority stress may lead to poorer mental health for sexual and gender minority adolescents, yet no interventions have been tested through an RCT to address these concerns. Methods We report on an RCT of an intervention-Proud & Empowered-with four high schools. Measures assess the intervention's impact on mental health symptoms. Results Compared to the control, participants in the treatment condition reported significant differences in minority stress, anxiety, and depressive symptoms. Moderation analyses showed that the intervention significantly moderated the relationship between minority stress and PTSD (b = -1.28, p = .032), depression (b = -0.79, p = .023), and suicidality (b = 0.14, p = .012) symptoms; those in the intervention condition had mitigated relationships between measures of stress and health outcomes compared to those in the control condition. Conclusions Results suggest that Proud & Empowered help reduce mental health symptoms and exposure to minority stressors and build coping strategies. Trial Registration The intervention was registered on clinicaltrials.gov on August 1, 2019 under Trial # NCT04041414 .